Simultaneous treatment of risk and resilience - Sandra König (Adapting to the Future: How Digitalization Shapes Sustainable Logistics and Resilient Supply Chain Management. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 31, 2021)
Purpose: Supply chain management has a clear focus on risk management, but recent developments have shown that it is also important to pay attention to resilience. This paper introduces a systematic approach to simultaneously treat the two correlated quantities and can incorporate various notations of risk and resilience. Methodology: A game theoretic model that allows simultaneous risk minimization and resilience maximation is proposed. Integration of existing supply chain risk and resilience measures is described to show its applicability. The intrinsic uncertainty of consequences of actions is explicitly taken into account by probabilistic payoffs. Findings: The model provides a set of actions that provide optimal protection, depending the weight put on risk vs. resilience (i.e., how much weight is put on which of the two goals). The problem of putting such theoretical results into practice is discussed and illustrated with an example. Originality: This work aims at improving existing best practice techniques to increase resilience by providing a systematic optimization method. It allows integration of existing resilience measures and is thus flexible to use.
urn:nbn:de:gbv:830-882.0161855; hdl:10419/249608; https://econpapers.repec.org/RePEc:zbw:hiclpr:31
Keywords: 650; Supply Chain Risk Management; Supply Chain Security